IMPLEMENTASI PEMBELAJARAN BERBASIS PROJECT-BASED LEARNING UNTUK MENINGKATKAN KETERAMPILAN ABAD KE-21 (KRITIS, KOLABORASI, KREATIVITAS, KOMUNIKASI) - Nurhayatii; Irma Yendi; Ena Suma Indrawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
21st-century education demands learning that is not only oriented towards mastering knowledge, but also on developing higher-order thinking skills and holistic competencies of students. 21st-century skills, including critical thinking, collaboration, creativity, and communication (4C), are essential competencies that must be developed in an integrated manner through the learning process. One learning model that is considered relevant in responding to these demands is Project-Based Learning (PjBL), because it emphasizes active, contextual, and student-centered learning. This study aims to comprehensively examine the implementation of Project-Based Learning in improving students' 21st-century skills. The study used a qualitative approach with a literature study method on various relevant primary and secondary literature sources. Data collection was carried out through systematic searches in national scientific databases, while data analysis used content analysis techniques combined with thematic synthesis. The results of the study indicate that Project-Based Learning consistently makes a positive contribution to improving students' critical thinking, collaboration, creativity, and communication skills. PjBL encourages students to actively engage in authentic problem-solving, collaborate in groups, generate creative ideas and products, and communicate learning outcomes systematically. Compared with conventional learning, PjBL is more effective in simultaneously integrating the development of 4C skills. The effectiveness of PjBL implementation is greatly influenced by teacher readiness, authentic assessment strategies, and policy and institutional support. Strengthening educator competencies and learning support systems so that PjBL can be implemented optimally and sustainably to improve the quality of 21st-century education.